Original article Some markers of neuronal damage in cerebrospinal fluid of multiple sclerosis patients in relapse - Mitosek-Szewczyk, Krystyna; Gordon-Krajcer, Wanda; Flis, Dorota; Stelmasiak, Zbigniew (Folia Neuropathologica, 2011)
In this paper the performance of cerebrospinal fluid (CSF) protein biomarkers important for monitoring damage of brain astrocytes and neurons for MS is reviewed. We estimated neurofilament, tau and phospho-tau proteins, β-APP, Aβ, S-100B and neuron-specific enolase in CSF of MS patients during relapse. We noted elevation of neurofilament, tau and phospho-tau proteins, S-100B, neuron-specific enolase and c-terminal epitopes of β-APP; concomitantly decrease of Aβ was observed. These CSF biomarkers for MS relapse should reflect the central pathogenic processes in the brain, i.e., axonal and neuronal degeneration.